Effects and implementation of a minimized physical restraint program for older adults in nursing homes: A pilot study - Wang, Jun; Liu, Weichu; Li, Xuelian; Li, Luyong; Tong, Jinyan; Zhao, Qinghua; Xiao, Mingzhao (Frontiers in Public Health, 2022)
Purpose Physical restraint (PR) reduction interventions are currently exploring in developed regions with well-established welfare systems, whereas developing countries with fast population aging have not attracted enough attention. This China's pilot study evaluated the effects of a minimized PR program on restraint reduction and nursing assistants' knowledge, attitudes, intention, and practice toward PR and explored nursing assistants' experience of the program. Patients and methods This was a one-group, pretest, and posttest pilot trial with a nested qualitative descriptive study. A minimized PR program was obtained by summarizing the best evidence and was implemented in one Chinese nursing home with 102 older adults from December 18, 2020, to March 21, 2021. An educational program including three theoretical lectures and one operation training was first conducted for nursing assistants one-month period. The primary outcome was PR rate at 3 months. The secondary outcomes contained duration of restraints, types of restraints, the rate of correct PR use, the incidence of falls and/or fall-related injuries, and antipsychotics use at 3 months. Data on PR use and older adults' characteristics were collected through physical restraints observation forms and older adults' medical records. Nursing assistants' knowledge, attitude, intention, and practice toward PR were measured using the Staff Knowledge, Attitudes, and Practices Questionnaire regarding PR at 1 month. A semi-structured interview for two administrative staff and a focus group discussion with 13 nursing assistants were analyzed using content analysis to explore perspectives of intervention implementation at 3 months. Results There were a significant increase in knowledge, attitude, and practice and a decrease in intention of nursing assistants after 1-month educational intervention (P < 0.001). Furthermore, only the rate of correct PR increased and the duration of restraint in the daytime decreased significantly at 3 months (P < 0.05). There were no significant effects on PR rate and other secondary outcomes at follow-up. Qualitatively, nursing assistants demonstrated overtly supportive perspectives and that assistance from the program enhanced their knowledge and practice. They noted several challenges that impeded implementation. Conclusion The intervention has acknowledged some benefits and was valued by nursing assistants. Implementation barriers should be addressed before delivering in larger trials.